Analisis Peramalan Penjualan Produk Kaos Sablon (Studi Kasus: Home Industry Alva Cloth) - Sri Rahayu; Dian Hakip Nurdiansyah (Jurnal Ilmiah Wahana Pendidikan, 2022)
The purpose of this study is to compare the sales budget made by the company with the sales budget based on the least squares method. The results showed that there was an increase in the number of sales of screen printing t-shirts by 6,756 pcs per month from sales calculations carried out by the company's management, namely 5,611 pcs. Based on the results of the correlation analysis, it shows that there is a very strong influence from the sale of screen printing t-shirts using the least squares method because the correlation value (R) = 0.915 or 92% with the statement of correlation coefficient if the correlation value > 0.70 then the correlation is very strong. Company management needs to use the least squares method in making sales forecasts because this method is very accurate in describing the numbers in the calculation and can prevent errors in data entry, make data more accurate and can shorten the time to calculate sales trends that occur. has been determined.